2009
DOI: 10.1242/dev.036426
|View full text |Cite
|
Sign up to set email alerts
|

Enhancer-promoter communication at theDrosophila engrailedlocus

Abstract: Enhancers are often located many tens of kilobases away from the promoter they regulate, sometimes residing closer to the promoter of a neighboring gene. How do they know which gene to activate? We have used homing P[en]constructs to study the enhancer-promoter communication at the engrailed locus. Here we show that engrailed enhancers can act over large distances, even skipping over other transcription units,choosing the engrailed promoter over those of neighboring genes. This specificity is achieved in at le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
72
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 58 publications
(76 citation statements)
references
References 45 publications
4
72
0
Order By: Relevance
“…[46][47][48] Core promoter (TATA and DPE) and promoter proximal elements have been demonstrated in several cases to govern specificity in enhancerpromoter communication. [49][50][51] We reasoned that a defect in the pGawB Gal4 promoter region could account for the restricted reporting activity of ombP4 (compare ref. 46).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…[46][47][48] Core promoter (TATA and DPE) and promoter proximal elements have been demonstrated in several cases to govern specificity in enhancerpromoter communication. [49][50][51] We reasoned that a defect in the pGawB Gal4 promoter region could account for the restricted reporting activity of ombP4 (compare ref. 46).…”
Section: Resultsmentioning
confidence: 99%
“…63,64 and Drosophila genes. 51,[65][66][67][68][69][70] In the proximity hypothesis we posit that (1) pGawB but not PlacW or PGalW require proximity to promoter proximal elements in order to report the full spectrum of enhancer activity and that (2) omb P3 inserted at around 1.5 kb upstream of exon I does profit from such elements whereas omb P4 inserted 12 kb downstream of exon I and 2 kb upstream of exon Ia does not.…”
Section: Discussionmentioning
confidence: 99%
“…Chromatin capture studies show that enhancers and promoters are connected in highly complex condition-dependent patterns (6,15,17). Although core enhancer and promoter elements can provide some specificity (18), enhancers are often able to activate heterologous promoters if they are placed near to each other. Indeed, this lack of specificity is the basis for standard enhancer assays and screens (7,14,19).…”
mentioning
confidence: 99%
“…1A), because the efficiency of contact increases as the length of the DNA tether between the sites shortens (20)(21)(22)(23)(24). Promoter-tethering elements in Drosophila that allow activation by specific enhancers over long distances are proposed to form DNA loops between sequences near the enhancer and the promoter (18,25). In the mouse β-globin locus, the Ldb1 protein binds to proteins at the locus control region and at the promoter and appears to form a bridge necessary for efficient enhancer-promoter contact (26).…”
mentioning
confidence: 99%
“…Some examples of transvection at the Abdominal-B locus require a 10-kb sequence dubbed the transvection-mediating region (tmr) (Hopmann et al 1995), and transgenic studies have shown that the tmr can positively affect pairing (Ronshaugen and Levine 2004). Similarly, long-distance interactions between enhancers and promoters in cis can be facilitated by promoter tethering sequences (Zhou and Levine 1999;Calhoun et al 2002;Calhoun and Levine 2003;Lin 2003;Akbari et al 2008;Fujioka et al 2009;Kwon et al 2009). It is as yet unclear whether similar sequences are required for any enhancer to act in trans or, alternatively, whether transvection between regulatory elements is a natural consequence once chromosomes are physically paired.…”
mentioning
confidence: 99%